Lapsus calami, czyli „radość czytania” Barańczaka - Joanna Grądziel-Wójcik (Przestrzenie Teorii)
The article presents and interpretation of a Stanisław Barańczak’s poem Łono przyrody [The Bosom of Nature], seldom discussed by specialists. This seemingly simple poem from the volume Ja wiem, że to niesłuszne [I Know It’s Not Right] (1977) elaborates on the common idiomatic phrase ‘the bosom of nature’ and proves to be a masterful and intricate artistic declaration of existential and political disobedience. The “I” of Barańczak’s poem is something of a lapsus of Nature and History, standing in opposition to the mindless existence and enslavement of the communist state. In this sense he is very similar to the subject of Wisława Szymborska’s verse. Her poetic oeuvre, translated and discussed on numerous occasions by Barańczak himself, is indeed an important interpretive context here. The article points to the relationships between specific texts by both poets and depicts similarities and differences between their poetic outlooks.